Paragraph 3, Part Ii Of The Vienna Declaration And Programme Of Action 1993: A Reflection Of The Approach Of The Universalist Or The Cultural Relativist? - Mohamed Khalil, Nurhalida (Journal of Malaysian and Comparative Law, 2019)
Paragraph 3, Part Ii Of The Vienna Declaration And Programme Of Action 1993: A Reflection Of The Approach Of The Universalist Or The Cultural Relativist?